Characterization of a novel telomerase-immortalized human endometrial stromal cell line, St-T1b - Samalecos, Annemarie (BioMed Central, 2009)
BACKGROUND: Coordinated differentiation of the endometrial compartments in the second half of the menstrual cycle is a prerequisite for the establishment of pregnancy. Endometrial stromal cells (ESC) decidualize under the influence of ovarian progesterone to accommodate implantation of the blastocyst and support establishment of the placenta. Studies into the mechanisms of decidualization are often hampered by the lack of primary ESC. Here we describe a novel immortalized human ESC line. METHODS: Primary ESC were immortalized by the transduction of telomerase. The resultant cell line, termed St-T1b, was characterized for its morphological and biochemical properties by immunocytochemistry, RT-PCR and immunoblotting. Its progestational response was tested using progesterone and medroxyprogesterone acetate with and without 8-Br-cAMP, an established inducer of decidualization in vitro. RESULTS: St-T1b were positive for the fibroblast markers vimentin and CD90 and negative for the epithelial marker cytokeratin-7. They acquired a decidual phenotype indistinguishable from primary ESC in response to cAMP stimulation. The decidual response was characterized by transcriptional activation of marker genes, such as PRL, IGFBP1, and FOXO1, and enhanced protein levels of the tumor suppressor p53 and the metastasis suppressor KAI1 (CD82). Progestins alone had no effect on St-T1b cells, but medroxyprogesterone acetate greatly enhanced the cAMP-stimulated expression of IGFBP-1 after 3 and 7 days. Progesterone, albeit more weakly, also augmented the cAMP-induced IGFBP-1 production but only after 7 days of treatment. The cell line remained stable in continuous culture for more than 150 passages. CONCLUSION: St-T1b express the appropriate phenotypic ESC markers and their decidual response closely mimics that of primary cultures. Decidualization is efficiently induced by cAMP analog and enhanced by medroxyprogesterone acetate, and, to a lesser extent, by natural progesterone. St-T1b cells therefore serve as a useful model for primary ESC.